Mapping the market of unrefined forest industry by-products in northern Sweden - Persson, Léon (2022)
The forest industry plays an important role in the climate system. The need to reduce emissions of greenhouse gases is emergent, from a global perspective they are the driving force behind climate change. To reduce emissions, by-products from the forest industry can substitute fossil-based products. A global concern is the availability of by-products. And selection of business partners is of concern for the forest industry when it comes to refining by-product assortments. In this study the market for unrefined by-products in the four northern counties has been mapped and a balance between supply and demand for each county has been calculated. The data was collected from saw and pulp mills, public sources and from a transportation company. Further, the average cost of byproduct transportation per MWh was minimized, using a linear optimization model. The results from the optimization were then used to calculate the average transport distance for each by-product.. The results of this study indicate a deficit of by-products in Northern Sweden, and that demands are likely to increase. In addition, the results showed a variation of by-product production between the categories of sawmills and pulp mills. Variation was also found within the categories. The sawmill with the highest production, produced 40 % more by-products per m3sw than the one with the least production. The lumber yield makes a difference, but other factors are also important for share of by-products. These include integration with district heating, efficiency and assortment mix for the onsite sawmill boiler. Tree species and utilized technology at the supply unit, are other factors. A key conclusion in this study is that such factors affect the prerequisites for market supply calculations. Therefore, these factors need to be addressed, to adapt to the future market demand. By-product users can use the results as an information base for new investments, and to improve established business connections. Future studies should include larger sample sizes for demand and supply units, to determine what affects the market for and the production of by-products.